MOTION GRAPHIC RELATED TO WARNING ALERT ADVICE ON GATELESS RAILROAD CROSSING - Daniel, Kevin Oktavianus; Indahsari, Rina Dewi (VCD, 2021)
The motion graphic video design is aimed at drivers of two-wheel-drive and four-wheel-drive vehicles whose age is ranging from 17-40 years, with the length of a two-minute 15-second video that was released online. In the test results on 20 people with a targeted age range, about 94.4% of respondents responded favourably and 6.6% of respondents responded poorly. Therefore, it can be concluded that most of the respondents responded with a positive response to the motion graphic video related to warning alert advice on the gateless railroad crossing. Keyword: Accident, Gateless Railroad Crossing, Public Service Advertisements, Motion Graphic, Advice.